Aspiration, foreignness liability and market potential: How do they relate to small firms' international entrepreneurial orientation?. Issue 6 (12th November 2018) - Li, Lee; Qian, Gongming; Qian, Zhengming; Lu, Irene R.R.
Abstract : Purpose: Using behavioral theory of the firm, the purpose of this paper is to examine how a small firm's performance relative to historical and social aspirations is related to its international entrepreneurial orientation (IEO). This study also explores two environmental factors, liability of foreignness (LoF) and host-country market potential (HMP), as the moderators for the relationship of performance and IEO. Design/methodology/approach: This study uses survey for data collection from Canadian small firms and employs regression models for data analysis. Findings: The results show that small firms demonstrate stronger IEO when their performance is below aspirations, but their IEO diminishes when their performance exceeds aspirations. The authors also found that a small firm's LoF does not moderate the impact of its performance feedback on IEO. However, the authors found HMP plays a moderating role when a small firm's performance is below aspirations. Originality/value: This study investigates the relationship of IEO to aspiration and found that this relationship is moderated by HMP. The study advances our knowledge on small firms' international behavior.